Research of Zero Sequence Current of Parallel System of PWM Rectifier - NI Shuai; TANG Li-na; LIU Jie; NI Shi-jiang (Gong-kuang zidonghua, 2012)
Taking two-level parallel system of PWM rectifier as example, the paper analyzed cause of zero sequence circulation in parallel module: the circulation is generated by difference of duty cycle of zero sequence current of two modules; generation of the circulation has no correlation with size and type of load. It introduced implementation of control strategy of zero sequence current of parallel system of PWM rectifier based on k control and made simulation verification for the control strategy. The simulation result showed that k control can inhabit zero sequence current of parallel system of PWM rectifier but has no perfect inhabiting effect.